Gamma Radiation Induces p53-Mediated Cell Cycle Arrest in Bone Marrow Cells - Moraes, Andrea A. F. S.; França, Lucimar P.; Tucci-Viegas, Vanina M.; Lasakosvitsch, Fernanda; Gaiba, Silvana; Azevedo, Fernanda L. A.; Nogueira, Amanda P.; Segreto, Helena R. C.; Ferreira, Alice T.; Franca, Jeronimo P. (IntechOpen, 2012)
None